Terapi Humor untuk Menurunkan Intensitas Nyeri Pada Pasien Pasca Bedah Invasive - Awaludin, Sidik; Santoso, Agus; Novitasari, Dwi (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2016)
Surgery is a potential or actual threat to the integrity of the person both biopsychosocial and spiritual that can cause a response in the form of pain. Pain appears because the breakdown of network continuity. Unresolved pain may disrupt the healing process after surgery. Methods to overcome the pain to do the pharmacological and non-pharmacological. Non-pharmacological method that is often used to treat pain is distraksi.Distraction techniques can be done with humour therapy. Humour therapy done in several ways to see a funny movie, listen to the comic group, see cartoons, comics and caricatures are funny as well as reading a collection of funny stories. This study aims to determine the effect of humour therapy on pain intensity in patients with post-surgical minimally invasive second day. This study design is descriptives analysis. The number of samples in this study were 40 people. The sampling technique used is consecutive sampling. Analysis by viewing the presentation decrease in the frequency distribution table. The analysis shows the percentage difference in pain reduction in a larger scale in the treatment group. Humour therapy capable of reducing pain in patients with post-surgical minimally invasive second day.Keyword: invasive surgery, pain, humour therapy